PENDIDIKAN AGAMA HINDU DALAM PEMENTASAN WAYANG GEDOG PADA PELAKSANAAN UPACARA ATMA WEDANA DI DESA PAKRAMAN BERINGKIT KECAMATAN MENGWI KABUPATEN BADUNG - Anak Agung Adi Risanta Darma; Ni Kadek Sri Ekawati (Jurnal Pendidikan Agama, 2022)
The Wayang Gedog performance at the Atma Wedana ceremony in Pekraman Beringkit Village plays the play Bima Swarga which tells the story of Bima's journey full of obstacles in order to save Atma from his parents (Dewi Madri and Pandu). the implementation of the Pitra Yadnya ceremony is carried out in groups (mass), in this Wayang Gedog performance also facilities such as offerings and equipment are used to support the course of the performance. The stages carried out by Mangku Dalang in the Wayang Gedog performance are, performing prayers at Mangku Dalang's house to be protected during the performance, eating a meal, matur piuning which aims to ask permission to perform the performance, performing a performance which is divided into three acts, and making Tirta Sudamala on end of the show. The implementation of this ceremony aims to increase Pitara's status to Pitara God. The problems that will be discussed include: (1) What is the form of the Wayang Gedog performance at the Atma Wedana ceremony in Pakraman Beringkit Village, Mengwi District, Badung Regency?, (2) What is the function of the Wayang Gedog performance at the Atma Wedana ceremony in Pakraman Beringkit Village, sub-district Mengwi Badung Regency?, (3) What Hindu religious education values ​​are contained in the Wayang Gedog Performance at the Atma Wedana ceremony in Pakraman Beringkit Village, Mengwi District, Badung Regency?. The theory used to analyze the problem is the theory: Structural Functional Theory and Value Theory. The object of this research is the Wayang Gedog performance at the Atma Wedana ceremony in Pakraman Beringkit Village, Mengwi District, Badung Regency, while the subjects of this research are Mangku Dalang, Community Leaders, and the general public who know about the Wayang Gedong Performance at the Atma Weda Ceremony in Pakraman Beringkit Village, Mengwi District, Badung Regency. The data collection methods used in this study were the observation method, the library method, the interview method and the documentation method. The analytical strategy used in this research is descriptive qualitative. The results showed (1) the form of the Wayang Gedog performance, (2) the function of the Wayang Gedog performance, (3) the values ​​of Hindu religious education in the Wayang Gedog performance. The value of Hindu religious education contained in the Wayang Gedog performance at the Atma Wedana ceremony, namely: 1). Tattwa education, Tattwa education contained is about the nature of God's omnipotence as creator, preserver and fuse (Tri Kona) which is symbolized in Mangku Dalang. 2) Moral Education, the moral education contained is teaching to be able to be respectful towards parents, which can be done by doing and saying things that do not hurt parents' hearts. 3) Ceremonial education, the ceremonial education contained is to provide an understanding of the virtues of carrying out the Atma Wedana ceremony, so that in carrying out the ceremony, it can be done seriously as an effort to help the Atma from the ancestors so that later they can occupy a better place.